Multi-drug resistant Salmonella enterica serovar Typhi isolates with reduced susceptibility to ciprofloxacin in Kenya - Winnie C. Mutai (BMC Microbiology, 2018)
Abstract Background Typhoid fever remains a public health concern in developing countries especially among the poor who live in informal settlements devoid of proper sanitation and clean water supply. In addition antimicrobial resistance poses a major challenge in management of the disease. This study assessed the antimicrobial susceptibility patterns of Salmonella enterica serotype Typhi (S. Typhi) isolated from typhoid fever cases (2004–2007). Methods A cross sectional study was conducted on 144 archived S. Typhi isolates (2004–2007) tested against 11 antimicrobial agents by quality controlled disk diffusion technique. Isolates resistant to ampicillin, chloramphenicol, and cotrimoxazole were considered Multidrug resistant (MDR). Thirty MDR isolates were selected randomly and further tested using minimum inhibitory concentration (MIC) E-test. Results Sixteen percent (23/144) of the isolates were susceptible to all the antibiotics tested while 68% were resistant to three or more of the 11 antibiotics tested. The isolates showed a high susceptibility to ceftriaxone (94%) and gentamicin (97%). A high percentage of resistance was observed for the conventional first-line antibiotics; ampicillin (72%), chloramphenicol (72%), and cotrimoxazole (70%). Sixty-nine percent of the isolates (100/144) showed reduced susceptibility to ciprofloxacin. All the 30 (100%) isolates selected for MIC test were susceptible to amoxicillin-clavulanic acid. All except one of the 30 isolates were susceptible to ceftriaxone while majority 21 (70%) recorded an intermediate susceptibility to ciprofloxacin with MIC of 0.12–0.5 μg/mL. Conclusion A large proportion of S. Typhi isolates were MDR and also showed reduced susceptibility to ciprofloxacin. Fluoroquinolone resistance is emerging and this may pose a challenge in treatment of typhoid in future. There is need for routine surveillance to monitor this phenotype in clinical settings.